Sinyal Internet di Baduy: Dilema Antara Tradisi dan Modernisasi - Ratih Lestarini (LPPM Universitas Ekasakti Padang, 2023)
The Government's policy to increase the development of BTS provision and internet access throughout the territory of the Republic of Indonesia for economic development, especially as a result of the Covid-19 pandemic, is not without obstacles. On the one hand, the internet signal brings positive impacts through economic activities that are carried out efficiently and rationally, but for indigenous peoples such as the Baduy Tribe, Banten feels a negative impact with the entry of foreign values that damage the rules and social order in Baduy. Therefore, the Baduy Tribe applied for the removal of internet signals and the transfer of BTS from the Baduy customary land from various directions. There are two research questions, namely, 1) how Baduy Indigenous People respond to it, and 2) how Baduy local wisdom resolves the dilemma. The above questions are answered through the Socio-Legal method with legal sociology approach. This research is chosen because the author analyses the Government's policy and how the policy implementation for Baduy Tribe. The result of the research shows that Baduy Tribe strongly holds the tradition and ancestral belief system with the constancy of the behavior pattern that orientates to their belief system, has been able to solve their problems through local wisdom, they are willing to make adjustments to their customary law even though it is limited by allowing the existence of internet signals in Outer Baduy. The Government's decision to accept the application is also a decision to allow internet signals in Outer Baduy.